1999
DOI: 10.1152/ajpcell.1999.276.2.c337
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen modulates paracellular permeability of human endothelial cells by eNOS- and iNOS-related mechanisms

Abstract: Estradiol had a biphasic effect on permeability across cultures of human umbilical vein endothelial cells (HUVEC): at nanomolar concentrations it decreased the HUVEC culture permeability, but at micromolar concentrations it increased the permeability. The objective of the present study was to test the hypothesis that the changes in permeability were mediated by nitric oxide (NO)-related mechanisms. The results revealed dual modulation of endothelial paracellular permeability by estrogen. 1) An endothelial NO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 40 publications
6
30
0
Order By: Relevance
“…This proposal agrees with our recent findings that superoxide dismutase replenishment after injury decreases nitrotyrosine levels and rescues bioavailable nitric oxide from inducible nitric oxide synthase (19). Another report showed that micromolar, as opposed to nanomolar, estrogen concentrations used here led to vascular iNOS stimulation and deleterious effects (10). Although accurate estrogen levels could not be documented in our study due to profound interference with the immunoassay, our concentrations were safely below low nanomolar levels (consistent with the observed absence of detection by HPLC at the ~1 µM detection limit; data not shown).…”
supporting
confidence: 93%
“…This proposal agrees with our recent findings that superoxide dismutase replenishment after injury decreases nitrotyrosine levels and rescues bioavailable nitric oxide from inducible nitric oxide synthase (19). Another report showed that micromolar, as opposed to nanomolar, estrogen concentrations used here led to vascular iNOS stimulation and deleterious effects (10). Although accurate estrogen levels could not be documented in our study due to profound interference with the immunoassay, our concentrations were safely below low nanomolar levels (consistent with the observed absence of detection by HPLC at the ~1 µM detection limit; data not shown).…”
supporting
confidence: 93%
“…On the other hand, simple E2 exposure (1 -2 days) was found to increase the expression of iNOS in rat aorta (183) and in cultured endothelial cells (184). However, since these latter data were obtained under conditions not associated with inflammation, their relevance to the present discussion is limited.…”
Section: Effect On the Inducible Nitric Oxide Synthase And Other Inflmentioning
confidence: 69%
“…This paradox may be explained either by the different conditions in which NOdependent endothelial permeability was studied or by differences in NO levels. Moderate NO concentrations may decrease permeability, whereas low (in the presence of NOS inhibitor) or high (in the presence of eNOS agonist) levels of NO may increase permeability [51,52]. Interestingly, the role of NO in endothelial permeability has been linked with NO-mediated changes in the cytoskeleton [31,50].…”
Section: Figure 3 Effect Of Triton X-100 Extraction On Enos Localizationmentioning
confidence: 99%